Project-based learning used for teaching electrical installations and lighting installations in architecture - Alicia Martinez Anton; Nuria Castilla Cabanes; Rosa Pastor Villa; Vicente Blanca Gimenez (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: This paper discusses the use of Project-Based Learning (PBL) in the subject "Acondicionamiento y Servicios 2", which is taught at the Escuela de Arquitectura at the UPV. Design/methodology/approach: Case study. Findings: The results show that the goals (motivation, improved learning outcomes, independent learning and connection with professional practice), which led to the introduction of this kind of learning, have been achieved. Research limitations/implications: This work has been proved in two groups of a subject. Therefore, conclusions are specifically related to this context and generalization is not proved. Practical implications: Increase motivation, improved learning outcomes, independent learning and connection with professional practice. Originality/value: This work confirms previous studies about the useful of PBL in engineering matters.
Keywords: 650; projects; cooperative work; formative assessment; motivation; electrical installations; lighting installations